REPRESENTASI DIASPORA SERUMPUN MELAYU DAN TIONGHOA ASIA TENGGARA DALAM MEDIA BARU (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2014)
AbstractThe study of people in Southeast Asia has its own uniqueness. Malay Serumpun ethnic and Chinese were dispersed naturally in the region now known as one of the rapidly growing area of the world today. People of Malays and Chinese in Southeast Asia allied initially migrated, and then the next generation was born and grew up in the region as their own home (original homeland). Community interacts, transacts, and expresses its existence directly and or through the media. The use of the Internet (new media) in a communication event has become part of their identity and lifestyle of the global community. These sites, blogs, and Facebook have become part of life where it seems diversity characteristics as the original. Moreover, for the young, personal blog sites and social networks now tend to be claimed as an integral part of life of the millennium generation.This paper attempt to capture the existence of Malay and Chinese diaspora as virtually, especially in Southeast Asia including of Indonesia, Malaysia, Singapore, and Brunei Darussalam. Their existence is interpreted in the context of historical values, characteristic physical appearance, language, clothes, cooking (cuisine), non-physical characteristics that include the presence of both ethnic dynamics in socio-political contestation, Asian values and religiosity. Various official website of the government shows less dominant caharacteristics of the virtual representation of ethnic Malays and Chinese. But on the social sites that appear quite expressive representation, both characteristics of ethnic and other symbols. Views can not be separated from both race attractions between forces in the region. The tendency of the identity claim may still exist in some communities, but the representation of the dominant community has now emerged is a part of the global community, in terms of English usage, fashion, and universal values. The presence of two large clusters of races is the result of their struggle in the fight for equality, independence, social dynamics, politics, and culture from the colonial and postcolonial domination of power, and is now a global power. Keywords: Southeast Asia Cultural Studies, Diaspora Serumpun Malay, Diaspora Tionghoa